Invitation to contemporary physics - Ho-Kim, Q. (Quang), 1938- (World Scientific, 2004)
This completely revised second edition of our hugely popular book invites the reader to explore ten of the most important areas of modern physics: Symmetry, Lasers, Superconductivity, Bose-Einstein Condensation, Nanoscience, Quantum Computation, Chaos and Fractals, Stellar Evolution, Particles, and Cosmology.